Management of Arsha (Hemorrhoids) Through Ayurveda -A Review - Mahajan, Amit; Gupta, Aman; Gupta, Sonia; Puri, Paramjeet (International Research Journal of Ayurveda & Yoga, 2021)
Hemorrhoids is a commonest problem due to modern life style. It is notorious for its chronicity recurrences and it has been described virtually from the beginning of medical history. Half of the humans generally experience one hemorrhoidal episode at some point during their lives. Hemorrhoidal term used generally refer for pathological viscosity of the hemorrhoidal veins due to increase pressure. Acharya Sushruta has described Arsha causes, types, sign and symptoms and treatment. Hemorrhoids hampers the normal physiological function of body. Management of Arsha (haemorrhoids) described in detail in Ayurveda like Bheshaj (medicines), Kshar Karma (Application of Alkaline paste), Agni Karma (Heat Burn Therapy) and Shastra Kalpana (Surgical intervention). In this review article describe the Ayuvedic management of haemorrhoids in detail according to Ayurveda.